Can Cities Activate Sleeper Species and Predict Future Forest Pests? A Case Study of Scale Insects - Steven D. Frank; Michael G. Just (Insects, 2020)
Sleeper species are innocuous native or naturalized species that exhibit invasive characteristics and become pests in response to environmental change. Climate warming is expected to increase arthropod damage in forests, in part, by transforming innocuous herbivores into severe pests: awakening sleeper species. Urban areas are warmer than natural areas due to the urban heat island effect and so the trees and pests in cities already experience temperatures predicted to occur in 50−100 years. We posit that arthropod species that become pests of urban trees are those that benefit from warming and thus should be monitored as potential sleeper species in forests. We illustrate this with two case studies of scale insects that are important pests of urban trees in parts of the US. Melanaspis tenebricosa and Parthenolecanium quercifex are geographically native to the US but take on invasive characteristics such as higher survival and reproduction and become disconnected from natural enemies on urban trees due to the urban heat island effect. This allows them to reach high densities and damage their host trees. Parthenolecanium quercifex density increases up to 12 times on urban willow oaks with just 2 °C of warming due to higher survival and adaptation to warmer temperatures. The urban heat island effect also creates a phenological mismatch between P. quercifex and its parasitoid complex, and so egg production is higher. Melanaspis tenebricosa density can increase 300 times on urban red maples with 2.5 °C of warming. This too is due to direct effects of warmer temperatures on survival and fecundity but M. tenebricosa also benefits from the drought stress incurred by warmer urban trees. These effects combine to increase M. tenebricosa density in forests as well as on urban trees at latitudes higher than its native range. We illustrate how cities provide a unique opportunity to study the complex effects of warming on insect herbivores. Studying pestilent urban species could be a pragmatic approach for identifying and preparing for sleeper species.